(untitled) (Research, Society and Development, 2023)
Objective: To analyze pediatrics hospitalizations for primary care sensitive conditions and their outcomes. Methods: This is a retrospective cohort study, the data was collected from the records of hospitalization of children aged between 0 and 14 years admitted for pediatric hospitalization between March 2019 and February 2020, who were admitted to the emergency department, considering the following variables: age, sex, reason for admission, place of admission, discharge outcomes and Hospitalizations for Sensitive Conditions to Primary Care, based on the Brazilian List of Hospitalizations for Sensitive Conditions. Data were recorded and analyzed in Excel®️ 2016 software. Results: It was observed that 172 (18%) hospitalizations were sensitive to Primary Care, with the highest frequency of cases related to problems in the respiratory system (53.19%). The data pointed out that hospitalizations are more recurrent in the first year of life (n=313/32%), with the highest percentage of male patients (n=550/57%) compared to females (n=419/43%), 857 (88.44%) were discharged and all deaths (n=4/0.4%) occurred in the Emergency unit. Conclusion: Results provide support for the management and organization of the health system and highlight the need to strengthen Primary Care.